The RELATIVE CLAUSE AND ITS TRANSLATION FOUND IN THE “HOUSEBOY AND MAID”: RELATIVE CLAUSE AND ITS TRANSLATION FOUND IN THE “HOUSEBOY AND MAID” - I Made Juliarta (Focus Journal : Language Review, 2021)
This research study focuses on English relative clauses and their translations into Indonesian found in the “Houseboy and Maid”. This study aims at finding out the types of English relative clauses found in the story “Houseboy and Maid” and the types of shifts occured in the translation process. The analysis used the theory of relative clauses that is proposed by Quirk (1985), Sneddon (1996) and the theory of translation shift proposed by Catford (1965). The process of collecting data is started by reading the entire data source in order to understand the story and observe the possibility of the data source that can be taken from the story “Houseboy and Maid”. The method of collecting data is firstly, the data source is  read to find out the types of English relative clauses. This research study indicates that there are two types of English relative clauses found in the story “Houseboy and Maid”, they are: Restrictive relative clause and non-restrictive relative clause. There are some types of relative clauses found in the data source. First, it can be seen that the types of English relative clauses found in the data sources are restrictive relative clause as subject, restrictive relative clause as object, restrictive relative clause as prepositional object, non-restrictive relative clause as subject, and non-restrictive relative clause as object. Secondly, the types of translation shifts that are found in the novel are as follows: structure shifts, level shifts, and unit shifts. This study intends to: (i) analyze the types of relative clauses and its constituent structure found in the data source, (ii) analyze the types of translation shifts of relative clause in the translation process from source language into target language.